Dietary fats and serum lipids in relation to the risk of ovarian cancer: a meta-analysis of observational studies - Zhang, Xu; Ding, Hong-Mei; Deng, Li-Feng; Chen, Guo-Chong; Li, Jie; He, Ze-Yin; Fu, Li; Li, Jia-Fu; Jiang, Fei; Zhang, Zeng-Li; Li, Bing-Yan (Frontiers in Nutrition, 2023)
Although numerous epidemiological studies investigated the association between dietary fat intakes or serum lipid levels and ovarian cancer risk, a consistent and explicit conclusion for specific dietary fats or serum lipids that increased the risk of ovarian cancer is not available. In this study, a systematic review and meta-analysis were conducted to assess the key dietary fats and serum lipids that increased the risk of ovarian cancer; Databases of PubMed, Web of Science, and EMBASE were searched for observational studies. A total of 41 studies met the inclusion criteria including 18 cohort and 23 case-control studies (109,507 patients with ovarian cancer and 2,558,182 control/non-ovarian cancer participants). Higher dietary intake of total fat (RR = 1.19, 95% CI = 1.06-1.33, I 2 = 60.3%), cholesterol (RR = 1.14, 95% CI = 1.03-1.26, I 2 = 19.4%), saturated fat (RR = 1.13, 95% CI = 1.04-1.22, I 2 = 13.4%), and animalfat (RR = 1.21, 95% CI = 1.01-1.43, I 2 = 70.5%) were significantly associated with a higher This is a provisional file, not the final typeset article risk of ovarian cancer. A higher level of serum triglycerides was accompanied by a higher risk of ovarian cancer (RR = 1.33, 95% CI = 1.02-1.72, I 2 = 89.3%). This meta-analysis indicated that higher daily intake of total fat, saturated fat, animal fat, and cholesterol as well as higher level of serum triglycerides were significantly associated with an increased risk of ovarian cancer.